Magnesium Alloys 2017
DOI: 10.5772/66182
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Applications of Magnesium Alloys

Abstract: Therapy in cardiovascular medicine often relies on implantation of prosthetic materials or application of stents. The diseases of many cardiovascular structures require their complete and immediate repair by utilising prosthetic materials. The ideal cardiovascular prosthesis involves good functional properties, capability of regeneration and does not activate the host's immune system. Ideally, the graft can be applied for a temporary use and degrades after a predefined period according to controlled degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 120 publications
(141 reference statements)
1
3
0
Order By: Relevance
“…However, bare magnesium alloy stents are notorious for rapid corrosion or biodegradation, leading to devastating effects described in Section 4.3. Hence, as magnesium-based biodegradable coronary stent implantation is highly regarded as a potential therapeutic application to coronary heart disease, one of the leading causes of death globally [79][80][81], extensive ongoing investigations centered around strategies to control its degradation rate [82,83]. The strategies proposed are consistent with our earlier discussion in Section 4.3.…”
Section: Cardiovascular Applicationssupporting
confidence: 65%
See 1 more Smart Citation
“…However, bare magnesium alloy stents are notorious for rapid corrosion or biodegradation, leading to devastating effects described in Section 4.3. Hence, as magnesium-based biodegradable coronary stent implantation is highly regarded as a potential therapeutic application to coronary heart disease, one of the leading causes of death globally [79][80][81], extensive ongoing investigations centered around strategies to control its degradation rate [82,83]. The strategies proposed are consistent with our earlier discussion in Section 4.3.…”
Section: Cardiovascular Applicationssupporting
confidence: 65%
“…Presently, there are limited applications for magnesium and its alloys in cardiovascular medicine, as they are primarily experimental or preclinical [79]. Magnesium and its alloys are being investigated for their suitability to replace bio-inert metallic implants in typical cardiovascular therapeutic applications.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…Presently, there are limited applications for magnesium alloys in cardiovascular medicine, as they are mostly experimental or preclinical [45]. Magnesium and its alloys are being investigated for its suitability to replace bio-inert metallic implants in typical cardiovascular therapeutic applications.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…As magnesium-based biodegradable coronary stent implantation is a therapeutic application to coronary heart disease, one of the leading causes of death globally [45][46][47], it is extensively investigated today. Though it is a promising biomaterial, early in vivo trials have demonstrated mixed clinical outcomes [47].…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…PEO is a process that creates a rough, hard, and dense ceramic coating on lightweight metal construction materials, such as magnesium. In addition, the PEO process provides increased resistance to wear and corrosion, thermal stability, dielectric properties, improved bioactivity, and biocompatibility suitable for medical applications [4]. The PEO process involves anodic electrochemical dissolution, the combination of metal ions with anions to form ceramic compounds, and spark-induced condensation on the substrate [5].…”
Section: Introductionmentioning
confidence: 99%